Embodied Intelligence in Soft Robotics Through Hardware Multifunctionality - Cianchetti, Matteo (Frontiers in Robotics and AI, 2021)
The soft robotics community is currently wondering what the future of soft robotics is and it is therefore very important to identify the directions in which the community should focus its efforts to consolidate its impact. The identification of convincing applications is a priority, especially to demonstrate that some achievements already represent an attractive alternative to current technological approaches in specific scenarios. However, most of the added value of soft robotics has been only theoretically grasped. Embodied Intelligence introduced new principles, underlining the fundamental role of body characteristics, but at the cost of a dramatic increase of its design complexity. Thus, a pragmatic application of these principles still remains difficult and very limited. A different design approach could be beneficial, a more “open” design enabled by hardware able to fulfil multiple functionalities and synergies. This could be the key to effectively exploit Embodied Intelligence in soft robotics and to enable new abilities.